Type III restriction endonuclease EcoP15I is a heterotrimeric complex containing one Res subunit with several DNA-binding regions and ATPase activity - Wyszomirski, Karol H. (Oxford University Press, 2012)
For efficient DNA cleavage, the Type III restriction endonuclease EcoP15I communicates with two inversely oriented recognition sites in an ATP-dependent process. EcoP15I consists of methylation (Mod) and restriction (Res) subunits forming a multifunctional enzyme complex able to methylate or to cleave DNA. In this study, we determined by different analytical methods that EcoP15I contains a single Res subunit in a Mod(2)Res stoichiometry. The Res subunit comprises a translocase (Tr) domain carrying functional motifs of superfamily 2 helicases and an endonuclease domain with a PD..D/EXK motif. We show that the isolated Tr domain retains ATP-hydrolyzing activity and binds single- and double-stranded DNA in a sequence-independent manner. To localize the regions of DNA binding, we screened peptide arrays representing the entire Res sequence for their ability to interact with DNA. We discovered four DNA-binding regions in the Tr domain and two DNA-binding regions in the endonuclease domain. Modelling of the Tr domain shows that these multiple DNA-binding regions are located on the surface, free to interact with DNA. Interestingly, the positions of the DNA-binding regions are conserved among other Type III restriction endonucleases.